53.6k views
5 votes
F (×)=-3×^3-2 g (×)=-3×-3 find (-3) and g (4)

1 Answer

7 votes
We assume you mean
.. f(x) = -3*x^3 -2
.. g(x) = -3*x^-3

Then
.. f(-3) = -3*(-3)^3 -2 = -3*(-27) -2 = 81 -2 = 79

.. g(4) = -3*4^-3 = -3/64

_____
It is helpful if you use ordinary lower-case letters for variables (except in some formulas where upper-case letters are used). The symbol "×" is used to signify multiplication, so leads to confusion when you try to use it for a variable. In plain text, the exponentiation operator is a caret (^), so x^2 means "x squared", for example. If the exponent is supposed to include an arithmetic operation, then it needs to be enclosed in parentheses, x^(3y-4), for example.
User Dreampowder
by
5.7k points